A case of systemic lupus erythematosus presenting as bilateral avascular necrosis of femur. (December 2016) - Adikari, Madura; Gunawardane, Aloka; Illangantilaka, Sachithra; Atukorale, Himantha; Rubasinghe, Jeevanie
Abstract Background Avascular necrosis occur as a result of diverse etiology. Chronic inflammatory conditions such as systemic lupus erythematosus considered as a recognize cause. Many cases were reported in systemic lupus erythematosus after treating with corticosteroids. We report a case of a corticosteroid naïve patient presented as bilateral avascular necrosis of femoral head and later progressed to a case of systemic lupus erythematosus. Case presentation A 26 year old lady presented with right sided hip pain and diagnosed as avascular necrosis of the femoral head. After 6 months she presented a similar pain in left hip, which revealed avascular necrosis of left femoral head as well. A probable cause for her clinical presentation could not be found after extensive clinical and laboratory evaluation. Patient reported high erythrocyte sedimentation rate persistently, and over the next few years progressed as a case of systemic lupus erythematosus. Conclusion Above case illustrated avascular necrosis could be an early musculoskeletal manifestation of systemic lupus erythematosus even in the absence of corticosteroid administration.